Implementasi Kebijakan Peraturan Daerah Kabupaten Gianyar Nomor 2 Tahun 2019 Tentang Pelestarian Cagar Budaya terhadap Pura Tirta Empul - Bhawanta, I Wayan Damuna Suga; Erawan, I Ketut Putra; Erviantono, Tedi (Jurnal Nawala Politika, 2022)
The quality of the implementation of a public policy can be used as an indicator in measuring the success of the political system. A political system will be declared successful and feasible, if the resulting policies are able to answer all existing problems. The vulnerability of the condition of natural cultural heritage is also an issue that also needs to be considered by policy makers. This research, furthermore, seeks to explain the implementation of a public policy of Gianyar Regency Regional Regulation Number 2 of 2019 concerning Cultural Conservation Preservation of Tirta Empul Temple located in Tampaksiring District, Gianyar Regency. As a form of seriousness in caring for and maintaining cultural heritage sites, the Gianyar Regency Government has allocated funds every year to carry out cultural preservation, development, and development of local wisdom and existing cultural heritage. The Gianyar Regency Government intensively also formed the 2019 Cultural Conservation Registration Team and the Appointment of Cultural Conservation Experts through two Gianyar Regent Decrees. However, the implementation of existing policies needs to be evaluated for its sustainability, because there are several policies that are considered not right on target and are solutions to existing problems.